Don't be afraid to set up your fish facility - McNabb, Adrian; Carl, Matthias (Zebrafish, 2012)
Most young researchers leaving the safe haven of postdoctoral life for the unchartered territory of a PI position are confronted with a multitude of new tasks. For those using fish as their favorite model system, this often includes the daunting task of setting up and running a fish facility. New PIs are expected to know everything about this, and are even asked in job interviews about the precise details of the facility they anticipate using. Consulting other laboratories, talking to experienced facility managers, and sifting through books and web material will certainly help but can be enormously time consuming and at times frustrating. You will likely receive conflicting advice or encounter information that is overcomplicated and out of date. In this report, we summarize our collective experience of five different fish facilities, and outline what we consider to be the essential steps for setting up and running a successful facility. We also include valuable tips and tricks such as an optimized protocol for brine shrimp hatching. Our aim is to help researchers spend less time worrying about the technical aspects of their facility so that they can focus on their main job—research.